Towards Building a Latin American Community on Integrated and End-of-Life Care - Collado, Claudia (2025)
The presentation outlines the development of a Latin American Community of Practice focused on integrated care and end-of-life support, grounded in the open table philosophy. This space aims to connect diverse forms of knowledge, promote collaborative work among professionals, communities, and institutions, and strengthen regional networks. Key principles include community engagement, cultural relevance, shared governance, and knowledge exchange, with the goal of building collective capacities and context-sensitive experiences across the region.